Analisis miskonsepsi siswa kelas V pada materi sifat dan perubahan wujud benda di SDN 1 Nagarawangi - Linda Safitri Indriyani Safitri; Ghullam Hamdu; Erwin Rahayu Saputra (IKIP Siliwangi, 2024)
In learning science, the concept is the goal of learning science itself. At the elementary school level students' understanding of science concepts is still low. It is important for educators to instill the correct concepts in students, because the concepts taught in elementary schools will become the basis for students' thinking and will underlie students' thinking at the next level. The purpose of this study was to find out the misconceptions experienced by fifth grade students regarding the concept of the nature and changes in the shape of objects. The object studied was fifth grade students at SDN 1 Nagarawangi. Data collection was carried out by administering tests and interviews to fifth grade students. This research used a qualitative descriptive approach. Data collection techniques were obtained through diagnostic tests and interviews, then the data obtained was analyzed. Data analysis techniques used qualitative data analysis with the model from Milles and Huberman by means of data reduction, data presentation, as well as conclusions and verification of research data. The results obtained are that there are students who experience misconceptions about the concept of nature and changes in the form of objects in class V. The cause of this misconception is that it occurs because of students' associative thinking, the context that students get, wrong intuition and the way teachers teach.